High TSH concentrations in "euthyroidism": explanation based on control-loop theory. Issue 6067 (16th April 1977) - Wilkin, T J; Storey, B E; Isles, T E; Crooks, J; Beck, J S
Abstract : High concentrations of thyroid-stimulating hormone (TSH) in the serum have often been reported in apparently euthyroid patients with damaged thyroids. We have confirmed this finding in 14 patients 18 months after subtotal thyroidectomy for Graves's disease (group 1) and in 14 patients with manic-depressive psychosis (group 2) receiving lithium carbonate, which reduces thyroid reserve. One factor common to groups 1 and 2 but not to the controls was reduced thyroid reserve or functioning capacity, and, using established physical principles of servo-control, we have tried to define the mechanism. A series of curves were projected to indicate how TSH might be expected to vary with functioning thyroid capacity.